2009 IEEE Symposium on Industrial Electronics &Amp; Applications 2009
DOI: 10.1109/isiea.2009.5356375
|View full text |Cite
|
Sign up to set email alerts
|

The design of electrode-array for monitoring the cellular bioimpedance

Abstract: To real-time monitor the cell viability an important task in cell culturing associated applications. The bioimpedance spectroscopy is one of the useful techniques for this study. In this paper, a culture dish with an electrode-array is designed for the bioimpedance based cellular characterization. The electrode-array containing 32 electrodes is firstly fabricated using the Micro-ElectroMechanical-System (MEMS) technology, and then attached on the inner side of culture dish. Two types of current patterns of so-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Each gold-plated electrode had a width of 1.3 mm with a 6 mil gap between adjacent electrodes. Details of the design and performance of the electrode array were reported in 2009 [25]. In most studies on ECIS, the electrodes are designed to attach at the bottom of the culture plate [7,13].…”
Section: Multi-electrode Culture Monitoring Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Each gold-plated electrode had a width of 1.3 mm with a 6 mil gap between adjacent electrodes. Details of the design and performance of the electrode array were reported in 2009 [25]. In most studies on ECIS, the electrodes are designed to attach at the bottom of the culture plate [7,13].…”
Section: Multi-electrode Culture Monitoring Systemmentioning
confidence: 99%
“…Four-electrode measurement has been performed for the characterization of electrode-array cultures. Previous studies have reported that the adjacent method using fourelectrode measurement is applicable to distinguishing the influence of position error [25].…”
Section: Multi-electrode Culture Monitoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 0.5 ml of culturing medium with a density of 8.3 x 10 4 cells/ml PC12 cells are removed and poured into the culture dish. The novel culture dish with 32-electrode-array for real-time measuring the electrical property of cells was proposed and designed [7]. Load PC12 cell with RPMI 1640 medium in designed cultures and cultivate it in well conditioned incubation system for cell growth characterization.…”
Section: A Cell Preparation and Curlturingmentioning
confidence: 99%
“…In the last few years, many research efforts have been devoted to find a reliable and robust non-invasive technique to estimate and study cell growth on cell-culture assays [ 1 , 2 , 3 , 4 , 5 ] from different viewpoints. Many biomedical setups such as toxicology assays [ 6 ], cancer characterization experiments [ 7 , 8 ], biochemical [ 9 ], immune-assays [ 10 ], stem cells differentiation protocols [ 11 ], etc., seek to quantify the number of cells for characterizing a diversity of research objectives and techniques.…”
Section: Introductionmentioning
confidence: 99%